Employee Performance Analysis and Work Environment at the Front Office Department During the COVID-19 Pandemic at The ONE Legian Hotel - I Putu Wahyu Kusuma Dana (Jurnal Sains Terapan Pariwisata, 2021)
This study aims to analyze how the performance of employees and the work environment of employees in the front office department at The ONE Legian. Data collection methods used were observation, questionnaires, and interviews where data collection was carried out by field observations, questionnaires with 30 respondents. The analysis used quantitative analysis includes validity test, reliability test, correlation test, classical assumption test, simple linear regression test, determination coefficient test, and t test. The results of quantitative analysis research show that the reliability test results show that the work environment has a Cronbanch's Alpha value of 0.865 and employee performance has a Cronbanch's Alpha value of 0.810 which indicates that each variable has a value greater than Cronbanch's Alpha in the range of 0.70 in the correlation test. Correlation test of Employee Performance on the Work Environment in the front office department of The ONE Legian obtained a Pearson Correlation value of 0.745. In the simple linear regression analysis test results, the constant value is 14.089, which indicates that if the work environment is 0, then the employee's performance is 14.089. The value of the work environment coefficient is 0.678 indicating that if the work environment has increased by 1, then the employee's performance will increase by 0.678. With a strong and positive relationship between the two variables. Show that even during the COVID-19 pandemic, employees in the front office department at The ONE Legian can maintain their performance and work environment well.